Higher tibial quantitative ultrasound in young female swimmers. Issue 4 (23rd July 2004) - Falk, B; Bronshtein, Z; Zigel, L; Constantini, N; Eliakim, A
Abstract : Background: It has been found that swimming, a non-impact sport, generally has no effect on bone mineral density. Objectives: To examine bone properties, as measured by quantitative ultrasound, among female swimmers in comparison with control girls and women. Methods: Subjects included 61 swimmers and 71 controls aged 8.5 to 26.5 years. None of the swimmers was at the elite level and none had included resistance training in her schedule. Bone speed of sound (SOS) was measured bilaterally at the distal radius and the mid-tibia. Results: No differences were observed between swimmers and controls in body mass (mean (SD): 49.7 (12.3) v 50.7 (12.4) kg, respectively), although swimmers were taller (159 (12) v 155 (12) cm) and had lower body fat (18.3 (4.2)% v 22.3 (5.4)%). No difference was found in time since menarche (5.2 (4.0) and 4.5 (2.9) years in swimmers and controls, respectively; 21 swimmers and 25 control were premenarcheal). Radial speed of sound (SOS) increased with age but did not differ between swimmers and controls (non-dominant: 3904 (172) and 3889 (165) m/s for swimmers and controls, respectively). Tibial SOS also increased with age and was significantly higher in swimmers than in controls (non-dominant: 3774 (155) v 3712 (171) m/s). No differences were found between dominant and non-dominant sides. Conclusions: Swimming appears to be associated with higher bone SOS in the lower but not in the upper extremities. Further studies are needed to assess whether this difference reflects higher habitual activity among the swimmers or swimming specific mechanisms.